(untitled) (Journal of Technology and Operations Management, 2024)
The Digital Botanical Repository at Universiti Utara Malaysia (UUM) is an initiative designed to support the conservation and study of herbal plants, reflecting the region’s rich biodiversity. This repository aims to bridge the gap between the physical herbal plant garden and a wider audience by providing detailed plant profiles and advanced search functions online. The problem addressed by this study is the limited accessibility and engagement with the herbal plant garden’s resources. Despite the garden’s potential as a useful educational and research tool, physical access is limited, and there is a need for a more efficient way to disseminate information about the herbal plants it houses. The objective of the repository is to improve access to and engagement with the garden’s resources, enhance research capabilities, and support educational initiatives. By digitizing the plant information and making it available online, the project seeks to reach a broader audience and promote the garden’s use in various academic and research contexts. The methodology for developing the repository involved several key phases: conducting a requirement analysis to understand user needs, designing a database to store extensive botanical data and high-resolution images, creating a user-friendly and scalable interface, integrating the database with the interface, and implementing advanced search functionality. Usability testing was conducted using the Website Analysis and Measurement Inventory (WAMMI) framework to ensure a high standard of user experience. The findings from usability testing indicated that while users generally found the repository effective and engaging, there were issues with efficiency, error tolerance, and ease of learning. For instance, 49% of users agreed that the website seemed logical, but some experienced difficulties with navigation and search functionalities. The impact of this study is significant for botanical conservation and research. By addressing the identified usability issues and implementing suggested enhancements such as interactive educational tools, user-generated content, multilingual support, and collaborations with other botanical institutions, the repository can further its role as an invaluable resource.